Making use of Bragg’s diffraction for investigations of the acoustic activity of bismuth-germanium oxide - KLESZCZEWSKI, Z. (Archives of Acoustics, 1990)
The essence of the acoustic activity of crystals has been discussed. A measuring system for the investigation of this activity has been presented. The measuring method makes use of Bragg’s type diffraction of laser light in an acoustic wave. Measurements of the gyration constant G_23 for bismuth-germanium oxide have been made.